The NONEXPRESSOR OF PATHOGENESIS-RELATED GENES 1 (NPR1) and Related Family: Mechanistic Insights in Plant Disease Resistance - Backer, Robert; Naidoo, Sanushka; van den Berg, Noëlani (Frontiers in Plant Science, 2019)
The NON EXPRESSOR OF PATHOGENESIS-RELATED GENES 1 (NPR1) and related NPR1-like proteins are a functionally similar, yet surprisingly diverse family of transcription co-factors. Initially, NPR1 in Arabidopsis was identified as a positive regulator of systemic acquired resistance (SAR), paralogs NPR3 and NPR4 were later shown to be negative SAR regulators. The mechanisms involved have been the subject of extensive research and debate over the years, during which time a lot has been uncovered. The known roles of this protein family have extended to include influences over a broad range of systems including circadian rhythm, endoplasmic reticulum (ER) resident proteins and the development of lateral organs. Recently, important advances have been made in understanding the regulatory relationship between members of the NPR1-like protein family, providing new insight regarding their interactions, both with each other and other defense-related proteins. Most importantly the influence of salicylic acid (SA) on these interactions has become clearer with NPR1, NPR3 and NPR4 being considered bone fide SA receptors. Additionally, post-translational modification of NPR1 has garnered attention during the past years, adding to the growing regulatory complexity of this protein. Furthermore, growing interest in NPR1 overexpressing crops has provided new insights regarding the role of NPR1 in both biotic and abiotic stresses in several plant species. Given the wealth of information, this review aims to highlight and consolidate the most relevant and influential research in the field to date. In so doing, we attempt to provide insight into the mechanisms and interactions which underly the roles of the NPR1-like proteins in plant disease responses.